Distribution and high frequency of novel alleles at NF1 polymorphic markers in the Italian population - Natacci, F; Colapietro, P; Riva, P; Corrado, L; Rossi, LN; Maninetti, MM; Casciati, MC; Zambrino, CA; Lanzi; Larizza, L (Molecular and cellular probes, 1999)
Segregation analysis of Neurofibromatosis type 1 (NF1) intragenic polymorphisms is a useful diagnostic tool for linkage analysis in familial cases and for the exclusion/detection of deletion in sporadic patients. We performed a segregation analysis of intragenic NF1 polymorphic markers in an Italian NF1 population consisting of 17 familial and 41 sporadic cases, for a total of 79 affected and 105 unaffected individuals. The haplotype in linkage with the mutation could be identified in all of the familial cases. Furthermore, an intragenic deletion was found in one sporadic case and confirmed by means of FISH using an NF1 IVS27 specific probe generated by a novel PCR procedure. In order to determine the allele frequencies at four NF1 polymorphisms in the Italian population, the unaffected family members and 25 unrelated Italian individuals were genotyped. Allele frequencies were found to be statistically different from those in the literature for markers IVS27AC28·4 and IVS38GT53·0. In addition four novel alleles were found in four unrelated subjects, and we observed a mutation during paternal gametogenesis in one case. These data suggest that NF1 polymorphic intragenic loci are unstable. It is unclear whether or not their marked instability may enhance the high mutation rate of the NF1 gene.